Ankyloblepharon–ectodermal dysplasia–clefting syndrome misdiagnosed as epidermolysis bullosa and congenital ichthyosiform erythroderma: Case report and review of published work. Issue 5 (27th February 2019) - Zhang, Zhen; Cheng, Ruhong; Liang, Jianying; Lu, Zhiyong; Wang, Yirong; Li, Ming; Yu, Hong; Yao, Zhirong
Abstract: A Chinese female infant presented with ectodermal dysplasia, cleft palate and severe skin erosions at birth. Although all the typical clinical features of ankyloblepharon–ectodermal dysplasia–clefting (AEC) syndrome were present, the ankyloblepharon was not very marked. We misdiagnosed epidermolysis bullosa and congenital ichthyosiform erythroderma at first and confirmed the diagnosis of AEC syndrome only when she presented with the typical clinical manifestation of recurrent infected scalp erosions at 1 year of age. Mutation analysis of exon 13 of the p63 gene revealed a missense mutation Ile482Thr (c.1445T>C) in the sterile alpha motive domain. In this work we review the clinical features, differential diagnosis and prognosis in AEC syndrome.